The effect of perceived stress and specialization on the relationship between perfectionism and burnout in collegiate athletes. Issue 6 (2nd November 2018) - Garinger, Lindsay M.; Chow, Graig M.; Luzzeri, Matteo
ABSTRACT: Background: Athletic burnout is common when demands of the sport exceed the rewards. Individuals with certain personality dispositions, such as perfectionism, are at increased risk of experiencing perceived stress and subsequent burnout (Fender, L. K. (1989). Athlete burnout: Potential for research and intervention strategies. The Sport Psychologist, 3, 63–71. doi:10.1123/tsp.3.1.63 ; Gould, D., Tuffey, S., Udry, E., & Loehr, J. (1996). Burnout in competitive junior tennis players: I. A quantitative psychological assessment. The Sport Psychologist, 10, 322–340. doi:10.1123/tsp.10.4.322 ; Stoeber, J. (2011). The dual nature of perfectionism in sports: Relationships with emotion, motivation, and performance. International Review of Sport and Exercise Psychology, 4, 128–145. doi:10.1080/1750984x.2011.604789 ). Perfectionism has both adaptive and maladaptive dimensions, with the more maladaptive qualities leading to greater perceived stress (Hamachek, D. E. (1978). Psychodynamics of normal and neurotic perfectionism. Psychology, 15, 27–33.; Rice, K. G., & Van Arsdale, A. C. (2010). Perfectionism, perceived stress, drinking to cope, and alcohol-related problems among college students. Journal of Counseling Psychology, 57, 439–450. doi:10.1037/a0020221 ). Objectives: This study examined the influence of perfectionistic strivings and concerns on burnout, and perceived stress as a mediator of this relationship in Division II and III specialized and multiple-sport athletes ( N = 351). Design: Cross-Sectional. Methods: Participants completed a demographic questionnaire and online measures of perfectionism, stress, and burnout during the latter part of the competitive season. Results: Results showed a positive, direct effect of perfectionistic concerns on burnout. Stress partially mediated this relationship. Additionally, perfectionistic strivings had a negative direct effect on burnout for specialized athletes. Conclusion: The relationship between perfectionistic concerns and burnout is partially explained by stress. Multiple sport athletes showed lower levels of stress compared to specialized ones. Finally, perfectionistic strivings are associated with lower levels of burnout for specialized athletes.